Assessment of the CALLY Index, a Novel Immunonutrivite Marker, in Perioperatively Treated Gastric Cancer Patients - Orhun Akdoğan; Kadriye Bir Yücel; Ozan Yazıcı; Ahmet Özet; Nuriye Özdemir (Gazi Medical Journal)
Objective: This study aimed to investigate the prognostic significance of the C-reactive protein-albumin-lymphocyte (CALLY) index in patients with early-stage gastric cancer and compare it with other immune markers, such as systemic immune-inflammation index (SII), neutrophil lymphocyte ratio (NLR), and prognostic nutritional index (PNI). Methods: We retrospectively analyzed patients with early-stage gastric cancer who received adjuvant or perioperative chemotherapy. Laboratory results were obtained from the preoperative period. The CALLY index was calculated as follows: serum albumin level (g/dL) x absolute lymphocyte counts (109/L) / CRP (mg/dL) x104. Results: A total of 74 patients were included in the study. The median relapse-free survival (RFS) was 13.0 (95 %CI: 7.7-18.2) months in the low CALLY index group and 38.2 (95% CI:18.4-57.8) months in the high CALLY index group (p<0.001). The median overall survival (OS) was 25.0 (95% CI: 17.1-32.8) months in the low CALLY index group and 60.4 (95% CI:45.8-74.1) months in the high-CALLY-index group (p<0.001). In multivariate cox regression analyses, a low CALLY index was an independent risk factor for both relapse-free survival (RFS) and OS. Conclusion: The CALLY index was a prognostic factor for both RFS and OS, with a higher prognostic value than other prognostic factors (NLR, PNI, SII).